Biomimetic Carbon Sequestration and Cyanate Detoxification Using Heat-Purified Carbonic Anhydrase from Sulfurihydrogenibium yellowstonense - Chia-Jung Hsieh; Chia-Jung Hu; Chi-Yang Yu (Biomimetics, 2023)
The reaction condition for purifying carbonic anhydrase from Sulfurihydrogenibium yellowstonense (SspCA) by direct heating without prior cell lysis was optimized; heating at 70 °C for 5 min resulted in the highest total activity of 23,460 WAU (Wilbur–Anderson unit) from a 50 mL culture. Heat-purified SspCA was examined for its capability to increase the rate of the mineralization of CO2; compared with an uncatalyzed control, the onset time of CaCO3 formation was shortened by up to 71%. Cyanase can be used to degrade toxic cyanate; however, one of the limitations of this biomimetic process is that the reaction needs HCO3− as a substrate. Heat-purified SspCA was combined with heat-purified cyanase from Thermomyces lanuginosus to alleviate the HCO3− dependence; in industrial wastewater, the HCO3− required was reduced by 50% when 0.75 WAU of SspCA was added. Heat-purified SspCA is stable at 4 °C; 88% of the initial activity was retained for up to five weeks. Partially purified SspCA can be obtained with ease and applied to a variety of applications.